BIOETHANOL PRODUCTION FROM SUGARCANE BAGASSE PRETREATED BY TRICHODERMA VIRIDE - Mizar, Muhammad (Journal of Applied Engineering Science, 2020)
Preservation of fossil fuels are currently depleting with the massive exploitation of fuels. In this condition, breakthroughs are necessary to produce alternative fuels. One of the breakthroughs is bioethanol. It is a renewable energy which is more effective than gasoline inasmuch it can increase combustion efficiency and reduce exhaust emissions. In this work, a bioethanol process was done by using sugarcane bagasse waste material which has a lot of lignin and cellulose content. The content was converted into bioethanol by utilizing a strong base to degrade lignin and T. Viride as cellulose-producing and S. cereviseae yeast as a sugar converter to bioethanol. This present research aims to find the best formula of bioethanol production based on sugarcane bagasse with variations in cellulose hydrolysis temperature, shaking speed, and fermentation time by using an integrated shaker machine fuzzy-logic control of temperature and humidity. This research employed a complete randomized design experimental research (CRD) to test temperature, speed, and time modification by using a shaker machine. The independent variables were : (1) temperature, (2) shaking speed, and (3) fermentation time. The dependent variables measured were reducing sugar and bioethanol levels. The results showed that the best formula for producing bioethanol levels was at a treatment temperature of 45℃ and a speed of 140 rpm with fermentation time of 48 hours which resulted in a bioethanol level of 2.75%.
Keywords: bioethanol; sugarcane bagasse; reducing sugar; pretreatment; microbial